The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/2047487313518473
|View full text |Cite
|
Sign up to set email alerts
|

Severely vitamin D-deficient athletes present smaller hearts than sufficient athletes

Abstract: Severely 25(OH)D-deficient athletes present significantly smaller cardiac structural parameters than insufficient and sufficient athletes. Future research should investigate the precise mechanism(s) causing cardiac hypertrophy with increases in serum 25(OH)D in healthy athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 25 publications
2
53
0
3
Order By: Relevance
“…Whilst studies around the globe have demonstrated that vitamin D insufficiency/deficiency is a health concern affecting athletes [2]; not all elite cohorts have exhibited clinical deficiency, in support of the current findings [15,16,17,18,19,20,21,22]. Unlike the majority of athletes, those competing at the elite level have access to a support network of dietitians that regularly monitor dietary intake and nutrient status by analysis of food diaries and blood screening.…”
Section: Discussionsupporting
confidence: 84%
“…Whilst studies around the globe have demonstrated that vitamin D insufficiency/deficiency is a health concern affecting athletes [2]; not all elite cohorts have exhibited clinical deficiency, in support of the current findings [15,16,17,18,19,20,21,22]. Unlike the majority of athletes, those competing at the elite level have access to a support network of dietitians that regularly monitor dietary intake and nutrient status by analysis of food diaries and blood screening.…”
Section: Discussionsupporting
confidence: 84%
“…Our group previously demonstrated no association between serum 25(OH)D and markers of bone health in weight bearing athletes of different racial background, suggesting that markers of bone health are independent of serum 25(OH)D concentrations 18. It appears there is a ‘paradoxical relationship’ between race and vitamin D concentration that has largely been ignored, that is, Black individuals generally have the lowest serum 25(OH)D concentrations but the greatest BMD and reduced risk of fracture 14 19.…”
Section: Introductionmentioning
confidence: 73%
“…For example, athletes and well‐trained individuals that participate in dynamic exercises such as long‐distance running have an increased cardiac output, driven by an elevated stroke volume and lower heart rate (McArdle & Katch ). Indeed, it is well‐established that the physiology of the heart is dependent upon the modality of sport, age, ethnicity, genetics and body composition (Allison et al ). Although research to date has not focused on the direct effects of vitamin D supplementation on healthy cardiac morphology, a cross‐sectional study conducted in 506 international professional athletes (football, handball, volleyball and basketball players) from Qatar found that those with a 25(OH)D concentration classed as ‘severely‐deficient’ or ‘deficient’ (<25 and 25–50 nmol/l, respectively) had a smaller aortic root, right atria, left atria diameters, intraventricular septum diameter, left ventricular diameter and left ventricular mass (Allison et al ), which are likely to negatively affect cardiac output.…”
Section: What Physiological Roles Does Vitamin D Play In Sport?mentioning
confidence: 99%